Food Price Volatility and Kitchen Emergency: Transforming Community Greenhouses as a Low-Cost Food Security Intervention - Ahmad Hafidz Lubis; Ahmad Ihwanul Muttaqin; Ihya’ Ulumuddin; Putri Nadiyatul Firdausi; Achmad Farid (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Syarifuddin Lumajang, 2025)
This community service article examines the transformation of village land into bamboo-paranet community greenhouses as a low-cost solution to reduce household expenditures and strengthen food security. The service methodology uses Participatory Action Research (PAR) and religious social capital as a replication protocol. The activities are carried out through the PAR cycle (to know, to plan, to action, to reflect), utilizing socio-economic mapping and income mapping, Focus Group Discussions (FGDs) using problem-tree and hope-tree analysis, and technical assistance for the development of bamboo-rack paranet greenhouses. Initial results indicate an increase in the availability of fresh kitchen supplies at the household level, strengthening the role of women in food management for both families and communities, and a reduction in daily household expenditures as reliance on the market for vegetables and spices decreases. Additionally, the integration of religious social capital has proven to enhance compliance with duty schedules and usage regulations. Pre–post quantitative data related to household expenditures and harvest volume will be presented in the final manuscript to measure the effectiveness of the community greenhouse model as a low-cost/high-impact intervention within the framework of the six dimensions of food security.